Cardiac MRI in the Diagnosis and Prognosis of patients with Hypertrophic Cardiomyopathy (HCM) - A Case Report - Neupane, Nirmal Prasad; Rajlawot, Kritisha; Koirala, Keshika; Phuyal, Subash (Nepalese Heart Journal, 2022)
Hypertrophic cardiomyopathy (HCM) is a condition of genetic mutation in the cardiac sarcomere that is defined by cardiac hypertrophy, a non-dilated left ventricle, and a normal or increased ejection fraction. It presents with a heterogeneous clinical picture which continues to challenge clinicians to diagnose it clinically. Cardiac magnetic resonance (CMR) - a non-invasive imaging technique is an essential diagnostic tool that reliably confirms the diagnosis, differentiates hypertrophic cardiomyopathy from other etiologies of left ventricular hypertrophy as well as identifies the individuals who are most at risk of sudden cardiovascular events. We present a case of 15 years old female patient with complaints of left-sided chest pain, dyspnea, palpitations, and orthopnea with a history of several episodes of syncopal attacks in the past. Following echocardiography, cardiac magnetic resonance imaging was done for the proper interpretation of the presenting clinical manifestations.